Vergleichsstudie von Systemansätzen für das Schnellladen von Elektrofahrzeugen - Johannes Schäuble; Silvia Balaban; Peter Krasselt; Patrick Jochem; Mahmut Özkan; Friederike Schellhas-Mende; Wolf Fichtner; Thomas Leibfried; Oliver Raabe (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2016)
One of the major challenges for a global success of electric vehicles is to meet customer's expectations to a user–friendly charging infrastructure. The technology of fast charging of electric vehicles offers electric vehicle users the opportunity to travel in excess of the car's range. Therefore, various system approaches and standards for fast charging of electric vehicles have been developed in several countries and by different manufacturers. Within the scope of this study existing approaches of system designs for fast charging of electric vehicles in different regions (China/Europe/USA/Japan) have been analyzed in terms of their technical, economical and legal feasibility. For this purpose the general system for fast charging has been defined and several evaluation criterions have been determined. Based on the system, the regarded system approaches have been compared due to their different features and abilities. To expedite the comprehensive implementation of the fast charging technology, it is recommended that the proponents of the different system approaches will work together to benefit from their respective experience. Consequently, they are able to accelerate the joint use of the large technically and economically useful potential of fast charging.
urn:nbn:de:swb:90-531484
Keywords: 330